CHALLENGES AND OPPORTUNITIES IN TEACHING ENGLISH BASED ON CEFR (B2) REQUIREMENTS - Yuldashova Umida Baxtiyar kizi (International Engineering Journal For Research & Development, 2022)
This article discusses the old methods, which do not meet modern requirements, not to apply them to students, to reduce the redundancy of material in improving their knowledge, to enrich the educational process with real and useful materials, textbooks.